If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6b + 5(1 + -1b) = -8b + 26 -6b + (1 * 5 + -1b * 5) = -8b + 26 -6b + (5 + -5b) = -8b + 26 Reorder the terms: 5 + -6b + -5b = -8b + 26 Combine like terms: -6b + -5b = -11b 5 + -11b = -8b + 26 Reorder the terms: 5 + -11b = 26 + -8b Solving 5 + -11b = 26 + -8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '8b' to each side of the equation. 5 + -11b + 8b = 26 + -8b + 8b Combine like terms: -11b + 8b = -3b 5 + -3b = 26 + -8b + 8b Combine like terms: -8b + 8b = 0 5 + -3b = 26 + 0 5 + -3b = 26 Add '-5' to each side of the equation. 5 + -5 + -3b = 26 + -5 Combine like terms: 5 + -5 = 0 0 + -3b = 26 + -5 -3b = 26 + -5 Combine like terms: 26 + -5 = 21 -3b = 21 Divide each side by '-3'. b = -7 Simplifying b = -7
| (2x-1)(x^2-3x+5)=0 | | 3(2x+1)+1+2x=3(2x+2)+x | | 2X^2-16X+64= | | 7y-9-4y+4=0 | | 1.2x=40.8 | | 0(2x-4)^-11/2 | | -5+x-9=15 | | -1/4a7/4a=-21 | | 3/5x-3=2.25 | | 0.4=0.75y | | -(-5-6n)-3(2n+3)=3 | | 3x+4=-2x-14 | | -12-1x=8-3x | | 5x-3y=10fory | | -6=m+(-25) | | 3x/4=2 | | 1.8q-4.3-2.3q=-1.5q-4.6 | | -6=my+(-25) | | 7x^2-21x+0=0 | | X+8+7=2x+15 | | 108=-4(-6x-3) | | -20=5+x | | 5x/6=0 | | 3(x+1)+1+2x=3(2x+2)+x | | -7(-4n-4)+2(n+5)=-22 | | (25x)/45=-65 | | 4x+12+5x=36+18x | | 35-5x=10x | | 3x=8-2(7-2x) | | -23+7+x=-19 | | U=6(8n+33)+7(n+1) | | 4y-8=2(y+6) |